An ontology for a model of manufacturing scheduling problems to be solved on the web - Varela, M.L.R. (2008)
In this paper we describe an ontology for a model of manufacturing scheduling problems to be solved on the web, through several different scheduling methods made available by a web scheduling decision support system.This approach aims enabling to share scheduling knowledge and methods, in a globally distributed context, in order to facilitate solving these problems, either in the industry or in the academic and research context. The proposed ontology is described in terms of basic objects, the scheduling problem attributes, in the form of problems characterization parameters; problem classes or types of scheduling problems and relations among problem classes; and problems instances.Finally, a sample of methods is presented for solving some well known problems arising in the scope of manufacturing scheduling. through the web.